Reliability of ultrasonography for diagnosing genital tract abnormalities in buffaloes - SAINI, J S; DHALIWAL, G S; GHUMAN, S P S; KUMAR, AJEET (The Indian Journal of Animal Reproduction, 2023)
The present work was planned to assess the reliability of ultrasonography in diagnosing genital tract abnormalities in non-gravid genitalia (n=505) of buffaloes collected from private abattoirs. Ultrasonograpil was done using 7 .5MHz linear probe after immersing genitalia in a water tub. Thereafter, genitalia were examined visually and were dissected with a scalpel blade to assess any abnormalities in the tubular tract/ovarian stroma. Grossly, abnormalities were observed in 53.70 percent genitf!lia. Sensitivity, specificity and predictive values of the ultrasonographic diagnosis in comparison to that of macroscopy/dissection concluded that reliabilit_x of ultrasonography was above 85 percent in diagnosing various genital tract abnormalities except for cervicitis and pyometra wherein sensitivity was low.